A case study of missed approach of aircraft due to tailwind associated with thunderstorms. (27th February 2012) - Tse, S. M.; Chan, P. W.; Wong, W. K.
ABSTRACT Two aircraft had to conduct missed approaches in the overnight period of 8–9 September 2010 due to intense thunderstorm activity at the Hong Kong International Airport (HKIA). The missed approach event is studied in detail in this paper using the available flight data and other meteorological measurements. It appeared that the missed approaches were attributable to strong tailwind associated with the downdraft of the thunderstorm. Timely wind shear/microburst alerts had been provided to the pilots in this case based on the measurements from a Terminal Doppler Weather Radar (TDWR) and ground‐based anemometer measurements at HKIA. The nowcasting and forecasting aspects for such an event are also discussed. The Aviation Thunderstorm Nowcasting System (ATNS) developed by the Hong Kong Observatory (HKO) is found to provide adequate nowcasting of thunderstorm activity for this particular case and the aviation weather forecasters could be alerted of such intense convective weather at the airport more than half an hour ahead. On the forecasting side, the mesoscale meteorological model used by HKO may provide an indication of the strong tailwind associated with the thunderstorm at 6–7 h ahead, though the exact timing of the tailwind at the airport may be delayed by a couple of hours compared with the actual situation. Using the model the downdraft of the thunderstorm in this event is examined in detail.